α-Glucosidase Inhibitory Activity of Ethanol Extract Obtained from Dillenia suffruticosa and Pycnarrhena cauliflora - Dzul Fadly (Journal of Global Pharma Technology, 2020)
The objective of the study was to find out the inhibitory of α-glucosidase activity and the antioxidant properties of an ethanol extract derived from leaves and stems of Dillenia suffruticosa and Pycnarrhena cauliflora. Dried powder of them was macerated with 96% ethanol solvents. α- Glucosidase inhibitory property was significantly demonstrated by the leaves and stems of D. suffruticosa. Antioxidant activity was found high in D. suffruticosa leaves and stems. The results indicate that D. suffruticosa stem may potential being antioxidant and antidiabetic compounds.Keywords: Dillenia suffruticosa, Pycnarrhena cauliflora, diabetes mellitus, α-glucosidase, ethanol extract.